MEMAHAMI KEMBALI PEMAKNAAN HADIS QUDSI - Idris, Abdul Fatah (International Journal Ihya' 'Ulum al-Din, 2016)
The scholars of hadith have different viewpoints in understanding the meaning of hadith Qudsi. The differences are affected by understanding of the concept of hadith Qudsi that is the the word of Allah conveyed through the words of the Prophet Muhammad. However, Hadith Qudsi is not like the Qur'an. This article will briefly show an understanding of hadith Qudsi and the Qur'an; and hadith Qudsi and Hadith Nabawi. The author agree with a view of the scholars of hadith who says that, the Hadith Qudsi is a special Hadith verbalized by Prophet both meaning and pronunciation. Therefore, there are no differences between Hadith Qudsi and the sayings of the Prophet in general. The Prophetic Hadith is classified into authentic hadith, hasan and da’eef; can also be found in hadith Qudsi. There may be some differences, in which Hadith Qudsi is not wider than Hadith Nabawi. Hadith Qudsi is not direct words of God, but only the ideas and then verbalized by the prophet himself.---Para ulama hadis memiliki sudut pandang yang berbeda dalam memahami makna hadits Qudsi. Perbedaan tersebut dipengaruhi oleh pemahaman konsep hadis Qudsi yaitu firman Allah yang disampaikan melalui firman Nabi Muhammad SAW. Namun, Hadis Qudsi tidak seperti Alquran. Artikel ini akan secara singkat menunjukkan pemahaman tentang hadits Qudsi dan Alquran; Dan hadis Qudsi dan Hadis Nabawi. Penulis setuju dengan pandangan para ulama hadis yang mengatakan bahwa, Hadis Qudsi adalah Hadis khusus yang diucapkan secara verbal oleh Nabi baik makna maupun pengucapannya. Oleh karena itu, tidak ada perbedaan antara Hadis Qudsi dan perkataan Nabi pada umumnya. Hadis Nabi diklasifikasikan ke dalam hadits, hasan dan da'eef yang otentik; Bisa juga ditemukan dalam hadis Qudsi. Mungkin ada beberapa perbedaan, di mana Hadis Qudsi tidak lebih luas dari Hadis Nabawi. Hadits Qudsi bukanlah kata-kata langsung dari Tuhan, tapi hanya gagasan dan kemudian diucapkan secara verbal oleh nabi sendiri.